CHATogether: a novel digital program to promote Asian American Pacific Islander mental health in response to the COVID-19 pandemic - Jae Eun Song; Nealie T. Ngo; Jessica G. Vigneron; Alan Lee; Steve Sust; Andrés Martin; Eunice Y. Yuen (Child and Adolescent Psychiatry and Mental Health, 2022)
Abstract Background In response to the COVID-19 pandemic and the associated rise in anti-Asian hate crimes, we developed the Compassionate Home, Action Together program, (CHATogether) to support the mental health of the Asian American and Pacific Islander (AAPI) community. CHATogether is a culturally informed and virtually delivered support program that harnesses the talents of AAPI teens, young adults, parents, and mental health professionals who share a commitment to serve their local communities. Methods Our objective was to identify the active components, optimal utilization, potential benefits, and pertinent limitations of the CHATogether program during the 3 years since its inception in 2019. By that time, the program had developed six distinct component arms: interactive theater, mental health education, research, peer support and community outreach, collaboration, and AAPI mentorship. To work towards this objective, we conducted a qualitative study using thematic analysis and an inductive approach based on grounded theory (GT), in which we analyzed anonymized transcripts of four focus groups, comprised of 20 program participants (11 females; 9 males). Results We developed a model of two overarching domains, each with three underlying themes: I. Individual stressors: (1) Family conflict; (2) Cultural identity; and (3) Pandemic impact; and II. Collective stressors: (1) Stigma related to mental health and illness; (2) Pandemic uncertainty; and (3) Xenophobia and societal polarization. Strengths of the CHATogether program include its role as a conduit toward AAPI connectedness and pride as well as purpose in building community. Through support and mentorship, the program cultivates a unique platform that promotes healing and resiliency in response to pandemic stressors and beyond. Conclusions CHATogether creates a safe space for the AAPI community. Through its methods of storytelling and encouraging creativity, CHATogether facilitates the discussion of challenging topics specific to the AAPI community. Given the national mental health crisis that is further being exacerbated by the COVID-19 pandemic, a digital prevention program such as CHATogether holds promise towards providing access to mental health resources and supporting early help-seeking behaviors for individuals in the AAPI community.